DISPARITAS EFISIENSI TEKNIS ANTAR SUB SEKTOR DALAM INDUSTRI MANUFAKTUR DI INDONESIA, APLIKASI DATA ENVELOPMENT ANALYSIS - Settings Etty Puji Lestari (LPPM Universitas Terbuka, 2007)
Efficiency is a parameter to measure performance quality of a company or agency, including manufacture industrial. One of tools was used to measure technical efficiency is Data Envelopment Analysis (DEA). This article attempts to investigate the existence of difference technical efficiency between sub sector in manufacture industry in Indonesia period 1990-2002 using DEA. This estimation result discovered that the generally performance of manufacture sector industrial in Indonesia growth in spanning perception 1990 and 2002 relative stabilize altought have decrease percentage of efficiency in economic crisis. On the contrary, these conditions do not followed by disparity efficiency growth between sub sectors which exactly experience of negative growth at perception period. The fact sign that policy strategy industrialize during the time not improve yet high level productivity, but on the other hand policy strategy industrialize during the time have enough succeeded to develop equity level between sub sector in manufacture industry